Purification of Two Nitrate Reductases from Xanthomonas maltophilia Grown in Aerobic Cultures - Ketchum, Paul A. (1992)
Xanthomonas maltophilia ATCC 17666 is an obligate aerobe that accumulates nitrite when grown on nitrate. Spectra of membranes from nitrate-grown cells exhibited b-type cytochrome peaks and A(615-630) indicative of d-type cytochrome but no absorption peaks corresponding to c-type cytochromes. The nitrate reductase (NR) activity was located in the membrane fraction. Triton X-100-extracted reduced methyl viologen-NRs were purified on DE-52, hydroxylapatite, and Sephacryl S-300 columns to specific activities of 52 to 67 μmol of nitrite formed per min per mg of protein. The cytochrome-containing NR(I) separated on sodium dodecyl sulfate-polyacrylamide gel electrophoresis into a 135-kDa α-subunit, a 64-kDa β-subunit, and a 23-kDa γ-subunit with relative band intensities indicative of a 1:1:1 α/β/γ subunit ratio and a M(r) of 222,000. The electronic spectrum of dithionite-reduced purified NR displayed peaks at 425, 528, and 558 nm, indicative of the presence of a cytochrome b, an interpretation consistent with the pyridine hemochrome spectrum formed. The cytochrome b of the NR was reduced under anaerobic conditions by menadiol and oxidized by nitrate with the production of nitrite. This NR contained 0.96 Mo, 12.5 nonheme iron, and 1 heme per 222 kDa: molybdopterin was detected with the Neurospora crassa nit-1 assay. A smaller reduced methyl viologen-NR (169 kDa), present in various concentrations in the Triton X-100 preparations, lacked a cytochrome spectrum and did not oxidize menadiol. The characteristics of the NRs and the absence of c-type cytochromes provide insights into why X. maltophilia accumulates nitrite.